Literature Review: Diagnosis and Management of Hypogonadism - Ayu, Ratu Asyifa Sukma; Setiawati, Sastraningsih; Nuha, Shofa Rona Alya; Nurjanah, Suci; Triani, Eva (Jurnal Biologi Tropis, 2024)
Hypogonadism is a clinical syndrome condition caused by disturbances in secretion at the hypothalamic-pituitary-gonadal level. In fact, regarding the results of examinations and decisions about hypogonadism treatment are still difficult to make. So, analysis of the diagnosis and management of hypogonadism in men and women needs to be studied. This research analyzes studies using the Google Scholar, Pubmed and Proquest databases. After searching, 995 articles were found. There were 14 articles containing the diagnosis and management of hypogonadism. Based on the search results, examining hormone levels is the gold standard for diagnosing hypogonadism in men and women. Treatment for primary and secondary hypogonadism for men and women can include sex steroid replacement, gonadotropin or GnRH replacement if the patient wants to increase fertility, surgical therapy and radiation therapy.